2013
DOI: 10.1089/aid.2012.0086
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biomarkers of Cardiovascular Risk Among HIV Type 1-Infected Adolescents: Role of Soluble Vascular Cell Adhesion Molecule As an Early Indicator of Endothelial Inflammation

Abstract: Cardiovascular disease (CVD) biomarkers were examined in a cohort of HIV-infected and HIV-uninfected adolescents who participated in Adolescent Trials Network study 083 utilizing samples from the Reaching for Excellence in Adolescent Care cohort, a longitudinal study of youth infected through adult risk behavior. Nonfasting blood samples from 97 HIV-infected and 81 HIV-uninfected adolescents infected by adult risk behaviors were analyzed for total cholesterol, low-density lipoprotein (LDL), high-density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
3
22
1
1
Order By: Relevance
“…This study assesses the activities of respiratory burst enzymes in order to ascertain if HAART impacts negatively or otherwise on these enzymes in HIV positive subjects on these drugs. It was observed from this study that there were significantly higher (p < 0.001) activities of CAT and myeloperoxidase in HIV positive subjects on HAART than HIV positive HAART naïve subjects, which was consistent with previous studies [22]. It was reported that myeloperoxidase activity was significantly higher in HIV infected subjects on HAART than HAART naïve subjects [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study assesses the activities of respiratory burst enzymes in order to ascertain if HAART impacts negatively or otherwise on these enzymes in HIV positive subjects on these drugs. It was observed from this study that there were significantly higher (p < 0.001) activities of CAT and myeloperoxidase in HIV positive subjects on HAART than HIV positive HAART naïve subjects, which was consistent with previous studies [22]. It was reported that myeloperoxidase activity was significantly higher in HIV infected subjects on HAART than HAART naïve subjects [22].…”
Section: Discussionsupporting
confidence: 92%
“…It was observed from this study that there were significantly higher (p < 0.001) activities of CAT and myeloperoxidase in HIV positive subjects on HAART than HIV positive HAART naïve subjects, which was consistent with previous studies [22]. It was reported that myeloperoxidase activity was significantly higher in HIV infected subjects on HAART than HAART naïve subjects [22]. But Ross et al [23] observed elevated myeloperoxidase activity in HIV infected adults both on HAART and HAART naïve.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…38 In the HIV population, VCAM-1 was significantly elevated in both HIV-infected adolescents who received antiretroviral therapy and who were treatment naive. 39 Other studies showed higher VCAM-1 and E-selectin levels in adult HIV patients with and without treatment, 40,41 and they were a potential marker of disease progression and death. 42,43 Recently, VCAM-1 was found to be associated with greater carotid intima media thickness in another study from our group.…”
Section: Discussionmentioning
confidence: 97%
“…У свою чергу, активація тромбоцитів пов'язана з ендоте-ліальною дисфункцією та в подальшому -з ремо-делюванням судинної стінки [2]. Зокрема, збіль-шення рівня молекул адгезії сприяє проникненню лейкоцитів у судинну стінку та накопиченню в ній ліпідів, що відображає ступінь пошкодження ендо-теліальних клітин і порушення мікроциркуляції в тканинах [9,17]. Це викликає розвиток ендотеліаль-ної дисфункції, яка вважається одним із чинників розвитку ІХС.…”
unclassified